Semi-solid reactive interfaces based on ZnO@C core-shell materials for zinc-iron flow batteries. (15th March 2022) - Zhang, Cunyin; Guo, Leibin; Deng, Chengwei; Huang, Haili; Cheng, Yuanhui
Graphical abstract: A multi-structured semi-solid anode with abundant electron-ion transfer networks was proposed to inhibit zinc dendrites and improve the cycling life of zinc-based flow batteries. Highlights: A multi-structured semi-solid anode was proposed to inhibit zinc dendrites. Developed anode has abundant electron-ion transfer avenues. Enables zinc-iron flow battery a long cycling life. Abstract: Aqueous zinc-based flow battery has advantages of low cost, high safety and abundant reservoir, showing a good application prospect. However, zinc dendrites remain a big issue to their cycling stability. Herein, we construct a multi-structured semi-solid anode by packaging multi-layered graphite felt and zinc slurry based on microporous carbon wrapped nano-ZnO (ZnO@MC). ZnO@MC is prepared by polymerizing dopamine on nano-ZnO and followed calcination. Microporous carbon shells act as restriction spaces, forbidding either oxidized or reduced zinc species flow out, but also serve as the first electron network. Meanwhile, carbon black and graphite felt function as the second and third electron networks. Besides, trace alkaline solutions deliver hydroxyl ions. Thus, the redox of zinc species proceeds in microporous carbon shells without zinc dendrites. Resultantly, semi-solid anode has high electrochemical activity and stability in zinc-iron flow batteries. The average efficiency is 74.8％ with negligible fluctuations over 840 h (460 cycles).